A Concept of Physical Reconfigurable Conveyor System - Abdul Rahman, A. A.; Muhamad, E.; Abdullah, S.; A. Rahman, M. A.; Osman, M. S.; Mohamad, N.R.; Noridan, N.Z. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Conveyor is one of the most important material handling equipment which able to transfer the product from one place to another. A concept of the physical reconfigurable conveyor system is developed in order to meet the market responsiveness at a reasonable cost with less maintenance cost and work. The concept of physical reconfiguration of the conveyor system is studied and the design of the concept for the physical reconfigurable conveyor system is modeled and verified by using design software using SolidWork. Different layouts are arranged by using the designed modular components. There are five requirements of the reconfigurable conveyor system had been proposed which are adjustable height, adjustable magnet lock, modularity, convertibility and short layout changeover time. In future, the prototype of the concept for the reconfigurable conveyor system can be developed in order to get a realistic result.